A study of dynamic behaviors of contact pair in lubricated ball linear guide. Issue 4 (8th May 2018) - Li, Linlin; Yang, Jiajun
Abstract : Purpose: This paper aims to predict the dynamic behaviors of contact between the steel ball and raceway in the elastohydrodynamically lubricated ball linear guide, thus providing a guidance for lubrication design for ball linear guide. Design/methodology/approach: Based on the point contact elastohydrodynamic lubrication (EHL) theory, the free vibration model of contact pair is presented to qualitatively analyze the effect of vibration on the film characteristics. The models of the film stiffness and damping coefficient under the EHL condition are built to investigate the effects of the working conditions on the dynamic parameters. The full numerical solutions are obtained using the multigrid technique. Findings: It is found that there exists damping from the decay of oscillations of the pressure and film thickness in the lubricated ball linear guide. Furthermore, the working conditions of the high load or low velocity can lead to the increase in the film stiffness in the steel ball-raceway contact, but there is a reverse variation trend for the film damping coefficient. Originality/value: The contact pair has been usually treated as dry in past studies on dynamics of the ball linear guide, and the damping is neglected. This research considers the actual lubrication and working conditions and predicts the dynamic behaviors of contact pair.